Strategi Pengembangan Kurikulum di Jamiah Islam Syeikh Daud Al-Fathani (Jisda) Yala Selatan Thailand - Mani, Sulfa; Ratnaningsih, Sita; Asy’ari, Hasyim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study discusses the curriculum development strategy at Jamiah Islam Sheikh Daud Al-Fathani (JISDA), Yala, Southern Thailand. The main focus of this study is to analyze the strategies implemented in the development of the curriculum to suit the needs of modern education and maintain Islamic principles. A qualitative approach is used in this study, with data collection methods through interviews, observations, and documentation. The results show that JISDA adapts various innovative strategies that combine religious and general science, and pays attention to local and global relevance. The main challenges faced are limited resources and adaptation to changes in Thailand's national education policy. This research provides recommendations for the development of a more responsive and sustainable curriculum in the future